MENINGKATKAN KETERAMPILAN LITERASI MENULIS TEKS PROSEDUR MENGGUNAKAN KOMBINASI MODEL PEMBELAJARAN PBL DAN PAP - Irma Febriana; Radiansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research uses Classroom Action Research which aims to improve teacher activity, student activity, writing skills and student learning outcomes using the Problem Based Learning (PBL) and Picture and Picture (PaP) learning model which is implemented in class IV at SDN Sungai Miai 4 Banjarmasin with a total of 22 students. Data collection techniques were carried out using observation and tests. The results of this research show that teacher activity at meeting 3 obtained a percentage of 96% with the criteria "Very Good". Student activity at meeting 3 obtained a percentage of 95.5% with the criteria "Very Active". Meeting 3's writing skills obtained a percentage of 86.4% with the criteria "Very Skilled". For classical completion of writing skills, "student learning outcomes at meeting 3 obtained a percentage of 95.5% with the criteria "Very Good". Based on the results of this research, it can be concluded that using a combination of PBL and PAP learning models can improve the quality of teacher activities, student activities, writing skills and student learning outcomes.